2014
DOI: 10.5430/ijhe.v3n4p129
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Finnish Student Teachers’ Practical Theories, Sources, and Teacher Education

Abstract: The purpose of this research is two-fold: 1) to describe what kind of practical theories student teachers have in the Finnish class teacher education context and 2) to analyse their differences and similarities at the initial and final phase of teacher education. We further analyse the relationship between the practical theories and their sources. The data include an e-form questionnaire with 1052 self-reported practical theories collected from 180 student teachers. The analysis of these theories is based on L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…The content of these PCTs' practical knowledge was mainly pedagogical and focused most often on essential principles of teaching and student learning processes, which indeed is the main mission of the teaching profession (Rosenshine, 1979). The majority of the practical knowledge in the present study was related to how to support students' learning processes with appropriate instructional decisions, when general education PCTs' practical knowledge was most often concerned with responsibilities of the teacher, instructional strategies, and classroom environment (Levin & He, 2008;Pitkäniemi et al, 2014). In addition, data from PETE students (Romar et al, 2018), which are comparable with this study, indicate that the instruction and teacher categories had about one third of each of the total DMs; while in the present study, the instruction category comprised 57% of the total and the teacher category comprised only 5%.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The content of these PCTs' practical knowledge was mainly pedagogical and focused most often on essential principles of teaching and student learning processes, which indeed is the main mission of the teaching profession (Rosenshine, 1979). The majority of the practical knowledge in the present study was related to how to support students' learning processes with appropriate instructional decisions, when general education PCTs' practical knowledge was most often concerned with responsibilities of the teacher, instructional strategies, and classroom environment (Levin & He, 2008;Pitkäniemi et al, 2014). In addition, data from PETE students (Romar et al, 2018), which are comparable with this study, indicate that the instruction and teacher categories had about one third of each of the total DMs; while in the present study, the instruction category comprised 57% of the total and the teacher category comprised only 5%.…”
Section: Discussionmentioning
confidence: 94%
“…Our review of these studies in both general education and PE shows that these researchers have concentrated on similar themes in analyzing PCTs' practical knowledge, such as teachers, teaching and instructional activities, classroom context, students, sociocultural aspects, and curriculum. In general education, PCTs' practical knowledge was most often concerned with responsibilities of the teacher, instructional strategies, and classroom environment (Levin & He, 2008;Pitkäniemi et al, 2014), whereas in PE, their practical knowledge focused mainly on instructional strategies and teacher responsibilities (Romar et al, 2018). Furthermore, Buitink (2009) noted that PCTs' well-developed practical knowledge showed a focus on students' learning processes and awareness of underlying principles of teaching.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The preservice teachers in this study showed a relative lack of focus on knowledge concerning curriculum aims and contextual issues related to school and society. This study clearly adds to the existing literature, especially in regard to the absence of practical knowledge related to how the curriculum and wider school context issues are related to teachers' work (Herold & Waring, 2011;Pitkäniemi et al, 2014;Stenberg et al, 2014). This finding clearly indicates that these preservice teachers were at the beginning phase of their professional socialisation.…”
Section: Dicussionmentioning
confidence: 58%
“…During the course (12 weeks), students had a chance to ask questions and were reminded several times to write down DMs as they appeared and not to leave the work to the last week (day) of the study course. While previous studies on preservice teachers' practical knowledge and beliefs have used a survey instrument to collect data from all participants during one specific occasion (Adamakis & Zounhia, 2016;Buitink, 2009;Levin & He, 2008;Maaranen et al, 2016;Pitkäniemi et al, 2014), He, Levin, and Li (2011) suggested that other data collection methods could be useful. So, informed by Black and Halliwell (2000), our intention was that preservice teachers should in writing construct their practical knowledge along with the coursework.…”
Section: Participants and Data Collection Methodsmentioning
confidence: 99%